2015
DOI: 10.1111/itor.12156
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of uncertain project duration and asymmetric risk sensitivity information in project management

Abstract: This paper investigates the impacts of uncertain project duration and asymmetric risk sensitivity information on the structure of incentive contract and profits in project management where a risk‐neutral project manager (she) engages a risk‐averse contractor (he) to complete a project. The project manager offers a duration‐based incentive contract to the contractor to ensure that he invests his effort to shorten the project duration and reports his risk sensitivity information truthfully. Within the framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 41 publications
0
18
0
3
Order By: Relevance
“…Using the framework of principal-agent theory, they investigate the impacts of information asymmetry on the optimal compensation contracts and the firm's profit. (K. Yang et al, 2016) investigates the impacts of uncertain project duration and asymmetric risk sensitivity information on the structure of the incentive contracts in a project with a risk-neutral project manager and a risk-averse contractor. In their problem, the project manager can offer a duration-based incentive contract to the contractor to ensure that he invests his best effort to shorten the project duration and reveals his risk sensitivity information truthfully.…”
Section: Incentive Contracts Under Information Asymmetrymentioning
confidence: 99%
“…Using the framework of principal-agent theory, they investigate the impacts of information asymmetry on the optimal compensation contracts and the firm's profit. (K. Yang et al, 2016) investigates the impacts of uncertain project duration and asymmetric risk sensitivity information on the structure of the incentive contracts in a project with a risk-neutral project manager and a risk-averse contractor. In their problem, the project manager can offer a duration-based incentive contract to the contractor to ensure that he invests his best effort to shorten the project duration and reveals his risk sensitivity information truthfully.…”
Section: Incentive Contracts Under Information Asymmetrymentioning
confidence: 99%
“…Li et al (2008) study airlines' optimal seat allocation for multiple fare classes given a differential cost structure of the competing airlines, and compare the competitive equilibrium with the possibility of collusion between airlines. Yang et al (2016) investigate the impact of uncertain project duration and asymmetric information about contractors' risk preferences on a project manager's optimal design of incentive contracts. None of these studies, however, extended the newsvendor model into a vertically related multilayer newsvendors setting as we do in this paper.…”
Section: Related Literaturementioning
confidence: 99%
“…Cakanyıldırım et al (2012) present an adverse selection model to analyze channel coordination with menu contracts to induce self-selection under asymmetric information, and they show that the optimal contract offered by the retailer depends on the size of the outside market that the retailer may serve. Yang et al (2016) investigate the impact of uncertain project duration and asymmetric information about contractors' risk preferences on a project manager's optimal design of incentive contracts. They find that the more volatile the project duration and the more risk averse the contractor is, the optimal incentive contract will lean more toward risk sharing relative to incentive provision, and also the project manager would be more willing to acquire information on contractors' risk preferences.…”
Section: Related Literaturementioning
confidence: 99%
“…Kolisch and Padman () have shown that not only makespan has been considered as objective in the RCPSP literature, but revenues, costs, resources leveling, and even uncertain project duration (Yang et al., ) impact project managers' (PMs) decisions. As they want to finish projects as soon as possible with maximum net present value (NPV) and minimum resource utilization levels, the RCPSP becomes an inherently multiobjective problem (Ballestín and Blanco, ).…”
Section: Introductionmentioning
confidence: 99%
“…The RCPSP has traditionally been solved as a single-objective problem with makespan as the most widely applied objective (e.g., Pritsker et al, 1969;Alcaraz and Maroto, 2001;Tormos and Lova, 2001;Hartmann and Briskorn, 2010;Kopanos et al, 2014;Koulinas et al, 2014). Kolisch and Padman (2001) have shown that not only makespan has been considered as objective in the RCPSP literature, but revenues, costs, resources leveling, and even uncertain project duration C (Yang et al, 2015) impact project managers' (PMs) decisions. As they want to finish projects as soon as possible with maximum net present value (NPV) and minimum resource utilization levels, the RCPSP becomes an inherently multiobjective problem (Ballestín and Blanco, 2011).…”
Section: Introductionmentioning
confidence: 99%